What Does a Definition of Death Do? (Diametros, 2018)
In his article, “Defining Death: Beyond Biology,” John Lizza argues in favor of a civil definition of death, according to which the potential for consciousness and social interaction marks us as the “kind of being that we are.” In this commentary, I critically discuss this approach to the bioethical debate on the definition of death. I question whether Lizza’s account is based on a full recognition of the “practical, moral, religious, philosophical, and cultural considerations” at play in this debate. I further propose that a truly ethical debate on definitions of death ought to concentrate on how different definitions of death are used in diverse contexts – what definitions of death do – and focus less on who has the right definition of death for all situations.
Keywords: brain death; culture; definition of death